Use of Digital Tools in Self-Monitoring of Thyroid Diseases: A Systematic Review of Available Solutions - Milić, Marko Kimi; Sinanović, Šćepan (Medical Gazzette, 2026)
Objective: To systematically review available digital tools for self-monitoring of thyroid diseases, with a focus on functionality, quality, and clinical validation. Methods: A systematic literature review was conducted following PRISMA guidelines, using the PubMed, Scopus, Web of Science, and IEEE Xplore databases for the period 2010–2025. The analysis included mobile applications, web platforms, and wearable devices designed for adults. The quality of the tools was assessed using the uMARS scale, which evaluates engagement, functionality, aesthetics, and information quality. Results: A total of 18 digital tools were identified. The most common features included symptom tracking (78%), laboratory result monitoring (67%), and medication logging (56%). The average uMARS score ranged from 3.8 to 4.5 (out of a maximum of 5). Only 28% of the tools were medically validated, while five were integrated with healthcare systems. The main shortcomings included the lack of personalized algorithms (22%) and unclear data protection policies (61%). Discussion: These tools enable real-time monitoring but lack standardization, clinical validation, and interoperability. Multidisciplinary collaboration between clinicians, developers, and regulatory bodies is essential. Conclusion: Digital solutions have the potential to improve self-monitoring of thyroid diseases but require more rigorous validation studies, better data protection, and personalized approaches.